2018
DOI: 10.1161/strokeaha.117.018844
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Identifies Patients Most Likely to Respond to a Restorative Stroke Therapy

Abstract: Percent CST injury is useful for predicting motor gains in response to therapy in the setting of subacute-chronic stroke. This measure can be used as an entry criterion or a stratifying variable in restorative stroke trials to increase statistical power, reduce sample size, and reduce the cost of such trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 40 publications
(55 reference statements)
3
64
4
Order By: Relevance
“…Our findings also indicated that tract/lesion overlap was not related either to performance on the proprioceptive or motor tasks. This is consistent with Cassidy et al () who investigated FA of the posterior limb of the internal capsule and motor recovery in a chronic stroke sample. Additionally, our findings are in agreement with Lindenberg et al () who reported that diffusivity changes were present in chronic stroke subjects with motor deficits even if the lesion did not directly overlap the tract.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings also indicated that tract/lesion overlap was not related either to performance on the proprioceptive or motor tasks. This is consistent with Cassidy et al () who investigated FA of the posterior limb of the internal capsule and motor recovery in a chronic stroke sample. Additionally, our findings are in agreement with Lindenberg et al () who reported that diffusivity changes were present in chronic stroke subjects with motor deficits even if the lesion did not directly overlap the tract.…”
Section: Discussionsupporting
confidence: 92%
“…Fractional anisotropy (FA) of the CST is considered a biomarker for predicting motor recovery after stroke (Boyd et al, ). Biomarkers, such as CST‐FA, are anticipated to one‐day guide treatment content and timing, as well as inform inclusion criteria for clinical trials (Boyd et al, ; Cassidy, Tran, Quinlan, & Cramer, ; Ward, ). The recommendation to include CST‐FA as a biomarker has largely resulted from two different types of studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to evaluating FA, MD, AD, and RD, we also examined the reliability of the normalized tract integrity values (FA ratio and FA asymmetry) since these values are commonly related to measures of behavior in chronic stroke (Borich et al, ; Cassidy, Tran, Quinlan, & Cramer, ; Lindenberg et al, ; Stewart, Dewanjee, Shariff, & Cramer, ; Stewart et al, ; Stinear et al, ). FA ratio and FA asymmetry values were reliable across time (ICC = 0.82–0.98), with the mean values reflecting a relatively small difference between ipsilesional and contralesional CST.…”
Section: Discussionmentioning
confidence: 99%
“…We did not include lesion volume as a covariate in the hierarchical regression analyses since CST Injury and lesion volume are likely collinear. We selected CST Injury, rather than lesion volume, as a biomarker of the structural integrity of the motor system since the former is a better predictor of motor recovery after stroke than the latter 7 , 8 , 51 , 52 . We assessed the influence of each covariate separately given statistical power limitations with a small sample.…”
Section: Methodsmentioning
confidence: 99%